Experimental investigation of hole expansion ratio for automotive-grade steels. (June 2023) - Chinara, Manaswini; Paul, Surajit Kumar; Chatterjee, Sudin; Mukherjee, Subrata
Hole expansion ratio (HER) is widely used to quantify the stretch-flangeability of sheet metal. HER is determined from the maximum limit of successful expansion of a central hole by a conical punch. The central hole edge is prepared by the punching process. Around 45° cracks are noticed at the central hole edge after successfully completing the hole expansion test. HER of punched hole correlates with uniaxial tensile properties like yield strength, ultimate tensile strength, total elongation, post-uniform elongation, and coefficient of normal anisotropy. Comparisons of strength (yield strength, ultimate tensile strength), anisotropy (coefficient of normal anisotropy) and deformation (total elongation, post-uniform elongation) parameters among steel grades are essential to relate HER among steel grades. Interstitial free steel is the highest, and SPFH steel is the lowest HER among the four steel grades. HER correlates nicely with the notch mouth opening displacement at peak load.